2012
DOI: 10.1080/10293523.2012.11082546
|View full text |Cite
|
Sign up to set email alerts
|

Empirical testing of the CAPM on the JSE

Abstract: Fama's (1970) efficient market hypothesis (EMH) and the capital asset pricing model (CAPM), jointly ascribed to Markowitz (1952), Treynor (1961), Sharpe (1964), Lintner (1965) and Moss in (1966, remain the foundation of most finance and investment courses. This is surprising, given the sustained criticism of the model and its assumptions, and is a reflection of the elegance and parsimony of the theory over the empirical evidence.On the Johannesburg Stock Exchange (JSE), several authors have examined and noted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 12 publications
2
27
1
Order By: Relevance
“…Furthermore, the five largest companies on the exchange make up approximately 40% of the index. Ward and Muller (2012) found that companies falling outside the ALSI are usually considered to be too small, and therefore too illiquid for most investors, which resulted in their exclusion from the index. Strugnell, Gilbert, and Kruger (2011) showed that a number of other share characteristics (i.e., anomalies) such as the size effect and price-earnings are correlated to betas.…”
Section: Figure 3: Summary Of the Sector Betasmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the five largest companies on the exchange make up approximately 40% of the index. Ward and Muller (2012) found that companies falling outside the ALSI are usually considered to be too small, and therefore too illiquid for most investors, which resulted in their exclusion from the index. Strugnell, Gilbert, and Kruger (2011) showed that a number of other share characteristics (i.e., anomalies) such as the size effect and price-earnings are correlated to betas.…”
Section: Figure 3: Summary Of the Sector Betasmentioning
confidence: 99%
“…Strugnell, Gilbert, and Kruger (2011) showed that a number of other share characteristics (i.e., anomalies) such as the size effect and price-earnings are correlated to betas. It was then established by Ward and Muller (2012) that small cap sectors have lower betas than their large and mid cap counterparts. Furthermore, it was discovered that low betas also relate to issues around liquidity, rendering concentration and liquidity constraints to be the two main factors associated with the observation of low betas.…”
Section: Figure 3: Summary Of the Sector Betasmentioning
confidence: 99%
“…The inclusion of the appropriate dividend component in the monthly total return calculation is achieved by spreading the periodic dividends across the full calendar year (as applied in Liew & Vassalou, 2000;Mutooni & Muller, 2007; some South African studies, such as Graham & Uliana, 2001, ignore dividends entirely). Transaction costs are not taken into account for two reasons: firstly, they arise almost entirely on an annual basis (as part of the annual portfolio rebalancing process), and secondly, they are approximately equal across all portfolios (points made, for example, by Ward & Muller, 2012). Therefore, for the purposes of this study transaction costs are immaterial, both in absolute amount and in terms of relative inter-portfolio differences.…”
Section: Measuring Portfolio Returnsmentioning
confidence: 96%
“…The findings of Van Rensburg and Robertson (), Strugnell et al . (), Ward and Muller () and Thomson and Reddy () all show that the standard version of the CAPM must be rejected for the SA market. Several researchers have considered Fama–French‐styled models for the SA market (see Auret and Cline, for an overview) while others have looked at an APT model that reconstructs SA indices from the underlying equity sectors (Kruger and Van Rensburg, ; Flint et al ., ).…”
Section: Modelling Of the Sa Equity Marketmentioning
confidence: 99%